A Fractional-Order Predator-Prey Model with Age Structure on Predator and Nonlinear Harvesting on Prey - Hasan S. Panigoro; Resmawan Resmawan; Amelia Tri Rahma Sidik; Nurdia Walangadi; Apon Ismail; Cabelita Husuna (Jambura Journal of Mathematics, 2022)
In this manuscript, the dynamics of a fractional-order predator-prey model with age structure on predator and nonlinear harvesting on prey are studied. The Caputo fractional-order derivative is used as the operator of the model by considering its capability to explain the present state as the impact of all of the previous conditions. Three biological equilibrium points are successfully identified including their existing properties. The local dynamical behaviors around each equilibrium point are investigated by utilizing the Matignon condition along with the linearization process. The numerical simulations are demonstrated not only to show the local stability which confirms all of the previous analytical results but also to show the existence of periodic signal as the impact of the occurrence of Hopf bifurcation.